Comparison of MRI in pediatric cochlear implant recipients with and without retained magnet. (June 2018) - Walker, Brian; Norton, Susan; Phillips, Grace; Christianson, Erin; Horn, David; Ou, Henry
Abstract: Objective: To report and compare medical, radiological, and audiological outcomes in pediatric cochlear implant recipients who underwent 1.5 and 3 Tesla strength MRI with and without retained magnet. Methods: Retrospective chart review at a tertiary care pediatric hospital and review of literature. Patients were identified via electronic medical records database search and were included if they had MRI after cochlear implant. Results: Of twelve instances of MRI in pediatric cochlear implant recipients at our institution, two minor complications and one major complication were recorded. The rate of complication was equal between patients who underwent MRI with and without retained magnet. All minor complications resulted from MRI with retained magnet whereas the only major complication resulted from magnet removal. Two novel complications are reported, including: magnet removal resulting in silastic tear necessitating reimplantation and magnet dislocation with spontaneous reduction. Magnet removal significantly decreased the size of artifact, but did not alter the diagnostic utility of the MRI. While audiological measures varied chronologically from MRI scans, they did not appear to be appreciably altered by MRI. Conclusion: MRI with and without magnet retention appear to carry risks of both major and minor complications. For the regions of interest for each scan, MRI quality was not appreciably altered by magnet status. Audiological measures appear unaffected by magnet status during MRI however, this may reflect natural variation.